Exon skipping in IspE Gene is associated with abnormal chloroplast development in rice albino leaf 4 mutant - Xu, Tingting; Zhang, Jingjing; Liu, Yiran; Zhang, Qiuxin; Li, Weiyan; Zhang, Yueling; Wu, Meifeng; Chen, Tong; Ding, Daochun; Wang, Wenyi; Zhang, Zemin (Frontiers in Plant Science, 2022)
The formation of leaf color largely depends on the components of pigment accumulation in plastids, which are involved in chloroplast development and division. Here, we isolated and characterized the rice albino leaf 4 (al4) mutant, which exhibited an albino phenotype and eventually died at the three-leaf stage. The chloroplasts in al4 mutant were severely damaged and unable to form intact thylakoid structure. Further analysis revealed that the candidate gene encodes 4-diphosphocytidyl-2-C-methyl-D-erythritol kinase (IspE), which participates in the methylerythritol phosphate (MEP) pathway of isoprenoid biosynthesis. We further demonstrated that the mutation at the exon-intron junction site cause alternative splicing factors fail to distinguish the origin of the GT-AG intron, leading to exon skipping and producing a truncated OsIspE in the al4 mutant. Notably, disruption of OsIspE led to the reduced expression of chloroplast-associated genes, including chloroplast biosynthetic and translation related genes and photosynthetic associated nuclear genes (PhANGs). In summary, these findings reveal that OsIspE plays a crucial role in chloroplast biogenesis and provides novel insights into the function of CMK during chloroplast development in rice.